Expression of the rice hoja blanca virus (RHBV) non-structural protein 3 (NS3) in Escherichia coli and its in situ localization in RHBV-infected rice tissues - Muñoz Fonseca, Miguel Eduardo (2004)
The non-structural NS3 protein gene from the rice hoja blanca virus (RHBV) was fused to the glutathione- S-transferase carboxilic end and expressed in Escherichia coli strain JM83. Large quantities of fusion protein were produced in insoluble form. The fusion protein was fractionated in SDS-PAGE and purified by electroelution, polyclonal antibodies were raised in rabbit and the antiserum was absorbed with bacterial crude extract. A band of similar size as that of NS3 protein was observed in Western blots using extracts from RHBVinfected rice plants. Immunoelectron microscopy with colloidal gold-labeled antibodies against NS3 protein and the viral nucleocapsid protein revealed in situ accumulation of NS3 protein in the cytoplasm but not in the viral inclusion bodies, vacuoles or chloroplasts of RHBV-infected plants, following the same pattern of distribution as the RHBV nucleocapsid protein.